STUDY OF THE JOINT MOVEMENT OF LIQUID FILM AND GAS - Avlakulov, Abdimazhit; Bazarov, Orifjan; Eshev, Sobir; Babajanov, Yuldosh (Innovatsion texnologiyalar, 2024)
When gas moves through a gas pipeline, in the case of significant speed, in many cases the flow stratifies in the form of an annular film of liquid. The article discusses issues related to the mode of movement of liquid or gas in pipelines, steam pipelines and gas pipelines. In particular, a simplified calculation method has been proposed to determine the effect of film on pressure loss in round pipes for laminar and turbulent fluid flow regimes.